Legitimidade, autoridade e hierarquia : as variações do pensamento político de Pedro de João Olivi (1279-1295) - Melo, Tiago Vieira de (2016)
In the second half of the XIII century, a friar of the Order of Minor took the theological panorama of the Medieval West, his name is Peter of John Olivi (≅1248-1298) and he ends up becoming a intellectual mind of a sparse dissent and divided the order of Friars Minor, dissent this known at the time by zealous. This study aims to understand the historicity of thought Olivi, in other words, the change that his thinking was going along his troubled life. The methodology is based on the work of Mark Bevir: The logic of the history of ideas, which seeks to rescue the historical meanings and subsequently reconstruct such ideas arising from the past. And for this, it is essential to have knowledge about the historical context in which these statements were made, since only then can we grasp the author's intention, because language changes with the passage of time and for such analysis becomes feasible, we will focus on certain examples of semantic meaning, related to an important point of discussion in the intellectual life of Olivi, his interpretation of plenitudo potestatis papalis. We will use as a documentary source Leuctra super Matthaeum (≅1279-1281) and De renunciatione papae (≅1294-1295). Analyzing these texts in the light of the stated methodology, we aim to understand the intellectual and even institutional pressures that shaped the way that the thought of Olivi was fit to be accepted, and check the implications of this framework in his works, as well as the reception the same for its most prominent players, that would result ultimately in the range of his thinking.